Cochlear inflammaging: cellular and molecular players of the innate and adaptive immune system in age-related hearing loss - Parekh, Shailee; Kaur, Tejbeer (Frontiers in Neurology, 2023)
Age-related hearing loss is the most common sensory disorder worldwide that contributes to numerous health conditions in the aging population. Despite its prevalence, current treatments, including hearing aids, are unsatisfactory in improving hearing deficits or slowing or reversing its pathophysiology. Immunosenescence is a key driver of neurodegenerative disease, and a similar mechanism has recently come to attention in age-related hearing loss. Imbalanced levels of cytokines and chemokines contribute to aberrant immune cell activity and a chronic pro-inflammatory microenvironment that may lead to degradation of inner ear structure and function. Macrophages, typically guardians of organ homeostasis, are found to develop dysregulated activity with aging due to unidentified factors, and they interact with other components of the innate immune system to damage sensory hair cells, synapses, neurons, and other structures of the inner ear critical to sensory signal transmission. They also increasingly trigger the inflammasome, a protein complex involved in inflammatory cell death, and the complement cascade, to perpetuate a cycle of inflammation and cellular damage in the cochlea, resulting in hearing loss. Senescence in certain T cell populations have indicated a role of adaptive immunity in age-related hearing loss as well. Deciphering the mechanisms of immune dysregulation is a critical first step in producing targeted therapies for hearing loss. This brief review describes the current and emerging research surrounding the dysregulation of the innate and adaptive immune systems in age-related hearing loss and its parallels with other neurodegenerative diseases.